Magnetic Particle Imaging for Dynamic Biological Event Tracking and Precision Theranostics - Linjun Wang; Yuehui Yuan; Benhui Hu (Bioelectromagnetics in Medicine, 2026)
Magnetic particle imaging (MPI) enables quantitative detection of superparamagnetic iron oxide nanoparticles with negligible tissue background and without ionizing radiation. By providing quantitative readouts of magnetic tracers, MPI offers a functional imaging approach for monitoring biological processes in vivo. With continued advances in tracer engineering, imaging systems, and reconstruction methods, MPI applications have progressively expanded from mapping tracer distribution and kinetics toward monitoring cell-associated processes, sensing microenvironmental changes, and guiding therapeutic interventions. We first summarize circulation- and organ-level applications, including vascular imaging, perfusion assessment, hemorrhage detection, and biodistribution monitoring, in which MPI primarily reports tracer location, quantity, and temporal dynamics. We then review cell-tracking applications, where labeled therapeutic cells, immune cells, or phagocytic inflammatory cells enable assessment of cell delivery, migration, homing, retention, infiltration, and clearance. Next, we examine responsive MPI probes that detect pathological cues, such as acidosis and reactive oxygen species, through changes in magnetic response. Finally, we highlight MPI-guided theranostic strategies, including magnetic hyperthermia, targeted drug delivery, release monitoring, and feedback control, with an emphasis on key challenges for clinical translation.